2015
DOI: 10.1007/s11111-015-0240-9
|View full text |Cite
|
Sign up to set email alerts
|

Marine protected areas and children’s dietary diversity in the Philippines

Abstract: Fish living around the coral reefs in the Philippines provide livelihoods for more than a million local fishers and are an important source of protein for coastal communities. However, this rich resource is at risk from myriad threats, which consequently threaten human livelihoods, nutrition, and health. In this paper, we examine the degree to which marine protected areas (MPAs), which aim to conserve marine biodiversity, are associated with improved nutritional outcomes in children under age 5. This analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Dietary diversity reflects the diversity of macro- and micro-nutrient intake [ 51 ]. Further, analyses in the Philippines suggest that access to protected marine resources can contribute to an overall improvement in dietary diversity, not just in fish consumption [ 12 ]. Unlike wasting and underweight; stunting is an irreversible condition [ 50 ], impacting cognitive ability, schooling, as well as health, employment and earnings in adulthood [ 52 54 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary diversity reflects the diversity of macro- and micro-nutrient intake [ 51 ]. Further, analyses in the Philippines suggest that access to protected marine resources can contribute to an overall improvement in dietary diversity, not just in fish consumption [ 12 ]. Unlike wasting and underweight; stunting is an irreversible condition [ 50 ], impacting cognitive ability, schooling, as well as health, employment and earnings in adulthood [ 52 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Responses are based on a 24 hour recall period. Our definition of dietary diversity is restricted to children between 6–35 months and parallels that of Johnson et al [ 49 ] and Alva et al [ 12 ]. Although the WHO restricts its dietary diversity score to children age 6–23 months [ 55 ], we use an expanded age range to explore the associations between marine biodiversity and child nutrition with a larger sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Darling [24] found that marine protected areas did not influence household food security (measured by protein consumption, diet diversity and food coping strategies) in coastal fishing communities in Kenya. On the other hand, Alva, Kiersten et al [25] found that living in close proximity (< two km) to a marine protected area in the Philippines was positively correlated with children's dietary diversity and intake of fish. Rather, the literature highlights that access, or one's entitlement, to food-rather than the aggregate availability of food per se-is crucial and yet is determined by a complex interplay of institutional, social, cultural and economic factors, and the broader health environment (including access to maternal and child health services, and water, sanitation and hygiene) [5,26].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have created a foundation to assess this relationship [e.g., (3, 8)]. Certain studies have examined the contribution of fish to overall dietary patterns [e.g., (9, 10)], and in some cases to nutrient intake, including micronutrients, vitamins, and protein [e.g., (11)] or linking to nutritional status as proxied by anthropometry [e.g., (12, 13)]. Our study differs in that it connects fisheries management practices to dietary patterns, nutrient intakes, anthropometric measures, and clinical biomarkers of micronutrient, vitamin, and fatty acid status.…”
Section: Introductionmentioning
confidence: 99%